2023
DOI: 10.1186/s12931-023-02532-0
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of CD147 inhibits cell proliferation, migration, invasion, lipid metabolism dysregulation and promotes apoptosis in lung adenocarcinoma via blocking the Rap1 signaling pathway

Ning Zhang,
Zhouzhong Liu,
Xuwang Lai
et al.

Abstract: Objective CD147 is an important glycoprotein that participates in the progression of diverse cancers. This study aims to explore the specific function of CD147 in lung adenocarcinoma (LUAD) and to reveal related downstream molecular mechanisms. Methods Followed by silencing of CD147, the viability, migration, invasion, and apoptosis of LUAD cells were measured by CCK8, wound healing, transwell assay, and flow cytometer, respectively. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…EMT of the tumor cells increases their ability to migrate and invade nearby tissues, eventually resulting in the formation of new metastatic foci [ 23 ]. Several studies have shown that CD147 is closely involved in cancer metastasis [ 24 26 ]. The results of our study reveal significant insights into the role of CD147 in breast cancer cell behavior and its potential impact on various cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT of the tumor cells increases their ability to migrate and invade nearby tissues, eventually resulting in the formation of new metastatic foci [ 23 ]. Several studies have shown that CD147 is closely involved in cancer metastasis [ 24 26 ]. The results of our study reveal significant insights into the role of CD147 in breast cancer cell behavior and its potential impact on various cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed various different pathways by which CD147 promotes tumor metastasis and invasion. Zhang et al reported that silencing of CD147 inhibited the migration and invasion of lung adenocarcinoma cells through blocking the Rap1 signaling pathway [ 24 ]. Dana et al’s data indicated that CD147 promotes the migration and invasion of cholangiocarcinoma cells by activating the Akt-FoxO3-NF-κB-MCT-1/4 axis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified that Figs. 1 and 2 were inadvertently swapped.…”
mentioning
confidence: 99%